Louis Untermeyer papers - Untermeyer, Louis, 1885-1977.; Untermeyer, Louis, 1885-1977.; Untermeyer, Louis, 1885-1977.; Untermeyer, Louis, 1885-1977.; Untermeyer, Louis, 1885-1977; Untermeyer, Louis, 1885-1977.
Correspondence, writings, and notebooks. Includes drafts or proofs of Modern American Poetry [and] Modern British Poetry (1962); Long Feud, Selected Poems (1962); The World's Great Stories: Fifty-five Legends that Live Forever (1964); Bygones: the Recollections of Louis Untermeyer (1965); and Labyrinth of Love (1965), based on Der Irrgarten der Liebe, by Otto Julius Bierbaum. The notebooks pertain to travels in Europe and within the United States and to Untermeyer's years as Library of Congress poetry consultant (1961-1963).
Poet, critic, and editor. Poetry consultant, Library of Congress.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Collection related to the Library of Congress Archives.
Keywords: Bierbaum, Otto Julius, -- 1865-1910.; Frost, Robert, -- 1874-1963.; Library of Congress; American poetry -- 19th century; American poetry -- 20th century; English poetry -- 19th century; English poetry -- 20th century; Legends; Poetry; Poets -- Correspondence, reminiscences, etc; Europe -- Description and travel; United States -- Description and travel; Critics; Editors; Poets